Gut Microbiota Dysbiosis Aggravates Mycoplasma gallisepticum Colonization in the Chicken Lung - Wang, Jian; Chen, Xueping; Li, Jichang; Ishfaq, Muhammad (Frontiers in Veterinary Science, 2021)
Mycoplasma gallisepticum (MG) is the pathogen that causes chronic respiratory diseases in chickens. Gut microbiota plays an important role in maintaining body health and resisting respiratory infection, but the correlation between gut microbiota and MG infection is poorly defined. Therefore, in this study, the correlation between gut microbiota and MG infection was explored by disturbing gut microbiota in chickens with antibiotic cocktail. The results showed that the gut microbiota dysbiosis impairs pulmonary immune response against MG infection. It has been noted that MG colonization in the lung was significantly increased following gut microbiota dysbiosis, and this could be reversed by intranasally administrated toll-like receptor 2 (TLR2) ligand, recombinant chicken IL-17 protein or recombinant chicken granulocyte–macrophage colony-stimulating factor (GM-CSF) protein. In addition, the levels of short-chain fatty acids (SCFAs) and vitamin A were significantly reduced in gut microbiota dysbiosis group, however, butyric acid or vitamin A as feed additives promoted MG clearance in the lung of gut microbiota dysbiosis group via increasing TLR2/IL17/GM-CSF and host defense peptides genes expression. The present study revealed an important role of gut microbiota in the defense against MG colonization in the lung of chicken.